Bronchiectasia and primary immunodeficiency associated with gastric neoplasm: A case report (Research, Society and Development, 2025)
Bronchiectasis is characterized by irreversible dilation of the bronchi, resulting in chronic lung dysfunction and multiple associated complications. There are several causes that can lead to its development, and with the advancement of imaging methods, diagnosis has become increasingly accurate and frequent, even in asymptomatic patients. The objective of this case report was to highlight the association between bronchiectasis in patients with common variable immunodeficiency (CVID) and an increased risk of developing gastric cancer. In addition to the typical pulmonary complaints of this condition, the patient also presented gastrointestinal symptoms. During further investigation, a diagnosis of gastric neoplasia was identified, which led to the indication of gastrectomy. The objective of this report is to alert to the higher incidence of neoplastic diseases in patients with bronchiectasis and CVID, highlighting the importance of early diagnosis. This awareness is essential for the adequate management of these conditions, promoting more effective monitoring and improving the patient's quality of life.